2023
DOI: 10.1186/s13098-023-00984-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic control and glucose fluctuation on in-hospital adverse outcomes after on-pump coronary artery bypass grafting in patients with diabetes: a retrospective study

Abstract: Background The optimal glycemic control level in diabetic patients undergoing coronary artery bypass grafting (CABG) with cardiopulmonary bypass (On-Pump) remains unclear. Therefore, this study aimed to investigate the effect of different blood glucose control levels and glucose fluctuations on in-hospital adverse outcomes in diabetic patients undergoing on-pump CABG. Method A total of 3918 patients with diabetes undergoing CABG were reviewed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…1. Finally, nine observational studies [16][17][18][19][20][21][22][23][24] were included in the meta-analysis.…”
Section: Results Of Database Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…1. Finally, nine observational studies [16][17][18][19][20][21][22][23][24] were included in the meta-analysis.…”
Section: Results Of Database Searchmentioning
confidence: 99%
“…Pooled results of nine studies 16 17 18 19 20 21 22 23 24 showed that a high acute GV was associated with an increased risk of MAE during hospitalization for patients after cardiac surgery (OR: 1.29, 95% CI: 1.15 to 1.45, p<0.001; Fig. 2a ) with mild heterogeneity (p for Cochrane Q-test=0.12, I 2 =38%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations